P018 Effect of CBT-I on sleep-wake state discrepancy in individuals with co-morbid insomnia and sleep apnoea: A randomised controlled trial. (9th November 2022) - Bensen-Boakes, D; Osman, A; Lack, L; Catcheside, P; Antic, N; Smith, S; Chai-Coetzer, C; O'Grady, A; Dunn, N; Robinson, J; McEvoy, D; Sweetman, A
Abstract: Introduction: Cognitive behavioural therapy for insomnia (CBT-I) is the recommended treatment for insomnia and improves insomnia symptoms. However, CBT-I effects on sleep-wake state discrepancy have not previously been examined in a sample of individuals with co-morbid insomnia and sleep apnoea (COMISA). This randomised controlled trial investigated the effect of CBT-I, versus no-treatment control, on sleep-wake state discrepancy in people with COMISA. Methods: 145 participants had their subjective and objective sleep parameters recorded at pre- and post-treatment via overnight sleep diaries and polysomnography. Results: Pre-treatment, individuals with COMISA significantly (p < 0.05) underestimated their sleep duration (M min = −51.9, SD = 94.1) and sleep efficiency (M % = −9.6, SD = 18.3) and significantly (p < 0.05) overestimated sleep onset latency (M min = 34.5, SD = 86.1). Post-treatment, there were significant reductions in sleep-wake state discrepancy parameters in both groups, but no significant interaction effects to support any differences between CBT-I versus waitlist control groups (all interactions, p > 0.367). Discussion: These findings suggest that treating the insomnia aspect of COMISA through CBT-I first may not be an effective method of reducing sleep-wake state discrepancy. This is possibly due to sleep apnoea being untreated, contributing to frequent awakenings and the discrepancy between perceived and polysomnography derived sleep parameters. Future studies could involve a COMISA group that receives treatment for their sleep apnoea symptoms before CBT-I.